Clinical characteristics and outcomes of patients undergoing surgeries during the incubation period of COVID-19 infection. (April 2020) - Lei, Shaoqing; Jiang, Fang; Su, Wating; Chen, Chang; Chen, Jingli; Mei, Wei; Zhan, Li-Ying; Jia, Yifan; Zhang, Liangqing; Liu, Danyong; Xia, Zhong-Yuan; Xia, Zhengyuan
Abstract: Background: The outbreak of 2019 novel coronavirus disease (COVID-19) in Wuhan, China, has spread rapidly worldwide. In the early stage, we encountered a small but meaningful number of patients who were unintentionally scheduled for elective surgeries during the incubation period of COVID-19. We intended to describe their clinical characteristics and outcomes. Methods: We retrospectively analyzed the clinical data of 34 patients underwent elective surgeries during the incubation period of COVID-19 at Renmin Hospital, Zhongnan Hospital, Tongji Hospital and Central Hospital in Wuhan, from January 1 to February 5, 2020. Findings: Of the 34 operative patients, the median age was 55 years (IQR, 43–63), and 20 (58·8%) patients were women. All patients developed COVID-19 pneumonia shortly after surgery with abnormal findings on chest computed tomographic scans. Common symptoms included fever (31 [91·2%]), fatigue (25 [73·5%]) and dry cough (18 [52·9%]). 15 (44·1%) patients required admission to intensive care unit (ICU) during disease progression, and 7 patients (20·5%) died after admission to ICU. Compared with non-ICU patients, ICU patients were older, were more likely to have underlying comorbidities, underwent more difficult surgeries, as well as more severe laboratory abnormalities (eg, hyperleukocytemia, lymphopenia). The most common complications in non-survivors included ARDS, shock, arrhythmia and acute cardiac injury. Interpretation: In this retrospective cohort study of 34 operative patients with confirmed COVID-19, 15 (44·1%) patients needed ICU care, and the mortality rate was 20·5%. Funding: National Natural Science Foundation of China.